6x^2-18x=0

Simple and best practice solution for 6x^2-18x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x^2-18x=0 equation:


Simplifying
6x2 + -18x = 0

Reorder the terms:
-18x + 6x2 = 0

Solving
-18x + 6x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '6x'.
6x(-3 + x) = 0

Ignore the factor 6.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(-3 + x)' equal to zero and attempt to solve: Simplifying -3 + x = 0 Solving -3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + x = 0 + 3 x = 0 + 3 Combine like terms: 0 + 3 = 3 x = 3 Simplifying x = 3

Solution

x = {0, 3}

 

See similar equations:

| 12x^2+8x+1=0 | | 3x+2=5x+14 | | 2(5x+7)=54 | | V^2+2v-3=0 | | -3(x+9)-(x-7)=16 | | p+30.34=22.87 | | 13=4x-19 | | y-4y+3=-30 | | 2(x-9)-5(x+6)=-12 | | 9x^2+45x=0 | | 72=4.5z | | -4(x+6)-3(x-8)=28 | | 9x^2-28=0 | | 2=3(x+7)+7x | | -3(2x+7)-2(3x-5)=25 | | 3(3x+4)=54+6x | | 6(2x+8)-4(8x-5)=-12 | | -7(x+8)+2(x-4)=-14 | | 3(x+7)-9(x+5)=18 | | 5x-8=4x+15 | | 9x+23+2x=4x+37 | | 3x-4y=-8 | | -2(4x+7)+6(5x-7)=10 | | -2(3z+7)=10 | | -8(3x+7)-2(5x-9)=-4 | | 4(5x+5)=-20 | | 7+4x+2+6=4 | | (-3y-5)-2y=2 | | 4x+7=x+13 | | 9n+7=-1 | | 8x+11(x+100)=3608 | | 4x+8=9x-17 | | 3x+12=7x-20 | | -4x+8=2x+12 | | 10+6n=n-5 | | (2t-3)(3t-2)=0 | | 5x+14=2x-7 | | onesixth*k=8 | | 5x-7=4x+23 | | x+38=112 | | 3y-2=2y+6 | | 7x-13=2x+12 | | 2n+3.4=n+5.2 | | 87a+92b=18 | | 6x^2-9x+5=0 | | 57a+83b=13 | | 2x^2+3x-4=0 | | 7x-16=26 | | 6(-3x-10)=-96 | | x^4-4x^2-12=0 | | 5(x-12)-2(x)=-9 | | 4x-9+3x=8x-1 | | 22-6x=40-8x | | 23x^2-35x+93=0 | | 12x^2-35x+93=0 | | 12d+6=18-48+9d | | x+3+x+6x=180 | | 3x+-4=x-6 | | -7+28m=26m-3g | | ax+bx+9=7 | | 99-9k=9k-9 | | 2x-4+6x=22-15+21 | | y=3-2x | | 2b-3=5b+1 | | 4-2a+8+5a=-9 |